Nursing staff stress from challenging behaviour of residents with dementia: a concept analysis. (4th July 2016) - Hazelhof, T.J.G.M.; Schoonhoven, L.; van Gaal, B.G.I.; Koopmans, R.T.C.M.; Gerritsen, D.L.
Abstract : Aim: Provide insight into the concept of stress in the context of challenging behaviour of nursing home residents with dementia and its causes and consequences. Background: Challenging behaviour is frequent in residents with dementia, but consequences for nursing staff are unclear. Introduction: Challenging behaviour of residents can be enervating for nurses and may lead to stress. Although stress in general is associated with negative outcomes, an overview of stress in this context would be a welcome addition to the field. Method: Concept analysis according to Walker and Avant. Results: Identified antecedents of stress: physical and verbal aggression, conflicts, excessive demands and being unresponsive (residents), age, experience, tenure, nursing level and training (nursing staff). Defining attributes: disturbed homoeostasis and the personal appraisal of the situation. Identified consequences regard health, psychological aspects and behaviour. Discussion: Intervening in the identified factors may contribute to prevention of stress in nursing staff. Limitations: Given a lack of strong empirical studies, our analysis is not based on a high level of evidence and needs to be tested. Papers from before 1990 might have been missed. Conclusion: The concept analysis revealed that nursing staff stress in the context of challenging behaviour may result from resident and nursing staff factors. Besides health and psychological consequences, behavioural consequences can enormously impact the well‐being of residents. Implications: Application in daily care to support teams in influencing resident and nursing staff factors could prevent stress, for instance using behavioural management training or recruiting higher educated nursing staff. Given the increasing complexity of care, creating specialized units with specifically trained staff for different groups of people with dementia may be desirable.